2003
DOI: 10.1242/dev.00483
|View full text |Cite
|
Sign up to set email alerts
|

TheC. elegansHand gene controls embryogenesis and early gonadogenesis

Abstract: The C. elegans genome encodes a single Hand bHLH transcription factor. Either hnd-1(RNAi) or a hnd-1 deletion causes partially penetrant defects in viability and gonadogenesis. Dead embryos and young larvae are often misshapen at the posterior end. Our primary focus has been the role of hnd-1 in gonadogenesis. Wild-type C. elegans has two somatic gonadal precursors and two primordial germ cells in stereotyped positions within its four-celled gonadal primordium. The hnd-1 gene affects the presence and position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 68 publications
6
87
0
1
Order By: Relevance
“…Interestingly, a synthetic lethal analysis using RNA interference (RNAi) and available mutants identified unc-120 interactions with both hlh-1 and hnd-1, suggesting these three factors might define a "muscle module" (Baugh et al 2005b). However, bodywall muscle development was not assayed in this study, and genetic studies failed to find interactions between hlh-1 and hnd-1 mutants affecting bodywall myogenesis (Mathies et al 2003). This suggested that the synthetic lethality observed between hlh-1 and hnd-1 in the RNAi screen may be due, in part or in whole, to defects in nonmuscle lineages.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…Interestingly, a synthetic lethal analysis using RNA interference (RNAi) and available mutants identified unc-120 interactions with both hlh-1 and hnd-1, suggesting these three factors might define a "muscle module" (Baugh et al 2005b). However, bodywall muscle development was not assayed in this study, and genetic studies failed to find interactions between hlh-1 and hnd-1 mutants affecting bodywall myogenesis (Mathies et al 2003). This suggested that the synthetic lethality observed between hlh-1 and hnd-1 in the RNAi screen may be due, in part or in whole, to defects in nonmuscle lineages.…”
mentioning
confidence: 87%
“…Previous studies of hnd-1 have described its expression and mutant phenotypes (Mathies et al 2003). Reporter gene studies showed a very dynamic pattern of hnd-1 expression in early embryos, including transient expression in most, if not all, bodywall muscle lineages.…”
Section: Hnd-1 Genetically Interacts With Both Hlh-1 and Unc-120mentioning
confidence: 99%
See 2 more Smart Citations
“…Using KpnI and XbaI, the FLP recombinase cDNA fragment was excised from pGC92 and ligated to KpnI/NheI-digested pPD118.26 or pPD118.28 (A. Fire, S. Xu, J. Fleenor, J. Ahnn and G. Seydoux, personal communication; http lag-2-promoter driven FLP recombinase plasmid pGC158 [P lag-2 T FLPTlet-858(39)]: We created a lag-2-driven FLP, pGC158, by replacing GFPTunc-54(39) from pJK590 (Blelloch et al 1999;Mathies et al 2003) between XmaI and ApaI with the FLPTlet-858(39) fragment cut from pGC94 with the same restriction enzymes.…”
Section: Vector Constructionmentioning
confidence: 99%